Essays on vertical integration, vertical contracts, and competitive effects - Millagaha Gedara, Nuwan Indika (Kansas State University, 2019)
This dissertation consists of two essays on vertical integrations that occurred in the U.S. Carbonated Soft Drink (CSD) industry, i.e., PepsiCo and Coca-Cola acquired their biggest bottlers. In 2010, the Federal Trade Commission (FTC) raised concern that Coca-Cola and PepsiCo's acquisition of bottlers may have anticompetitive effects in the CSD industry. This dissertation analyses the recent structural changes in the CSD industry to investigate competition by modeling the vertical structure of the upstream (e.g., manufacturers) and downstream (e.g., bottlers) level. The first essay empirically investigates how vertical integration impacts prices in the presence of common agency: a downstream firm may also produce and distribute an upstream rival’s products. We use the structural econometric models of demand and supply to analyze the recent structural changes in the CSD industry. Our results suggest that for products with eliminated double margins (Coca-Cola and PepsiCo), decreased prices. However, with regards to rival products (Dr Pepper Snapple Group), prices decreased for 12 oz 6 packs, and prices increased for 20 oz bottles. Specifically, the results show that vertical integration resulted in not only an anticompetitive effect but also a procompetitive effect. These mixed findings are consistent with the theoretical concern of pricing behavior in the presence of common agency and suggest caution when evaluating vertical integration in the CSD industry. The second essay analyzes the nature of competition by modeling the vertical contracts (linear and non-linear) between manufacturers and bottlers before and after the vertical integration. Our empirical findings suggest that during the respective pre-integration periods, Coca-Cola and PepsiCo each use nonlinear pricing contracts to supply their intermediate soft drink products to bottlers, with imposing retail price maintenance (RPM) under zero bottler margins. RPM is the practice whereby manufacturers make a contract with bottlers, that the bottlers will sell the manufacturer's product at certain prices. However, the post-integration period, upstream manufacturers that directly own downstream bottlers eliminated the double marginalization, whereas all other upstream manufacturers in the market actively compete in wholesale prices with rival manufacturers, leaving zero markups to their corresponding bottlers. Finally, we do not find evidence that manufacturers use different pricing contracts with bottlers for different product sizes (12 oz 6 pack and 20 oz bottles) during the pre-integration and post-integration periods.
Keywords: Vertical integration; Vertical contracts; Competitive effects